What determines the number of poverty-stricken people in Indonesia? - Manasika, Rina; Naomi, Agata Sandra; Utami, Rahayu Tri (Sebelas Maret Business Review, 2023)
Poverty is seen as a condition where basic rights are not fulfilled as a mandatory condition for carrying out a dignified life for the community. This research was conducted with the aim of analyzing and obtaining empirical evidence of how the provincial minimum wage (Upah Minimum Provinsi-UMP), Real Per Capita GRDP, and the open unemployment rate (Tingkat Pengangguran Terbuka-TPT) can affect the number of poverty-stricken people in Indonesia in 2020. The method used in this research is quantitative, namely the Ordinary Least Square (OLS) technique, with secondary data obtained from the official website source of the Indonesian Central Bureau of Statistics (BPS), which is processed using EViews 12 software.  The final results of the research showed that partially the UMP and Real Per Capita GRDP variables have a significant effect on the number of poverty-stricken people in Indonesia in 2020, while TPT has no significant effect. However, when all three variables were tested simultaneously, the results showed that there was a significant effect on the number of poverty-stricken people in Indonesia in 2020. Another result that was also shown in this study is the coefficient of determination (R2) at 0.7694 which means that 77% of the information needed to predict the dependent variable can be explained by all of the independent variables in this study.